Layered oxide positive electrode material and preparation method thereof, positive plate and sodium ion battery

By introducing specific additive element A into the positive electrode material of sodium ion battery and optimizing sintering conditions, the problem of CuO heterogeneous phase is solved, and the electrochemical performance and cycle stability of the battery are improved.

CN119133434APending Publication Date: 2024-12-13LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411258220.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The O3-phase layered oxide positive electrode material in sodium ion batteries is prone to CuO heterogeneous phases during the preparation process, resulting in a decrease in electrochemical performance and weakening of the magnification and cycle life.

Method used

By introducing a specific content of additive element A, the structural strength of the positive electrode material is changed, the dissolution of Cu elements is reduced, and the content of CuO heterophase is reduced. The mixed sintering method of nickel copper iron-manganese precursor and sodium source and dopant is used to control carbon The ratio of elements to sulfur elements is optimized, the sintering temperature and time is optimized, and the mass fraction of the copper oxide heterophase is below 0.5%.

Benefits of technology

The capacity, rate performance and cycling performance of the positive electrode material are improved, the electrochemical performance of sodium ion batteries is improved, and high capacity, good rate and cycling stability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133434A_ABST
    Figure CN119133434A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery positive electrode materials, in particular to a layered oxide positive electrode material and a preparation method thereof, a positive electrode plate and a sodium ion battery. The general formula of the layered oxide positive electrode material is NaxAyNi2 / 9Cu1 / 9Fe1 / 3Mn1 / 3O2; x is larger than or equal to 0.95 and smaller than or equal to 1.05, y is larger than or equal to 0.001 and smaller than or equal to 0.01, and A comprises at least one doping element of Sr, Ca, Ti, Zr, Mo, Nb, Bi, Sb, Y and B; and the mass fraction of the copper oxide impurity phase in the layered oxide positive electrode material is less than or equal to 0.5%. By introducing the additive element A with a specific content, the structural strength of the positive electrode material can be changed, the dissolution of the Cu element is reduced, the content of a CuO impure phase is reduced, and the electrochemical performance of the positive electrode material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a layered oxide positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art

[0002] Sodium-ion batteries have attracted widespread attention in recent years due to their abundant resources, affordable costs, and environmental friendliness. Among them, O3-phase layered oxide cathode materials have become the research focus of sodium-ion battery cathode materials due to their high capacity and good electrochemical performance.

[0003] Layered oxide cathode materials for sodium ion batteries are commonly prepared by the precursor method. However, the cathode materials prepared by sintering the nickel-copper-iron-manganese precursor with a high copper content with a sodium source are prone to CuO impurities. The inactive CuO impurities not only reduce the capacity of the material, but also lead to a decrease in its rate and cycle life, thereby reducing the electrochemical performance.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a layered oxide positive electrode material. By introducing a specific content of additive element A, the structural strength of the positive electrode material can be changed, the dissolution of the Cu element can be reduced, the content of the CuO impurity phase can be reduced, and the electrochemical performance can be improved.

[0006] The second object of the present invention is to provide a method for preparing a layered oxide positive electrode material, which has the advantages of short process, simple operation, and mass production.

[0007] The third object of the present invention is to provide a positive electrode sheet having high capacity, good rate performance and excellent cycle performance.

[0008] A fourth object of the present invention is to provide a sodium ion battery having excellent electrochemical performance, high capacity, good rate performance, and good cycle stability.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] The present invention first provides a layered oxide positive electrode material, the general formula of the layered oxide positive electrode material is Na x A y Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3O2; wherein 0.95≤x≤1.05, 0.001≤y≤0.01, A includes at least one doping element selected from the group consisting of Sr, Ca, Ti, Zr, Mo, Nb, Bi, Sb, Y and B; and the mass fraction of the copper oxide impurity phase in the layered oxide positive electrode material is ≤0.5%.

[0011] Furthermore, the ratio of the mass fraction C of the carbon element to the mass fraction S of the sulfur element in the layered oxide positive electrode material satisfies 1.5≤C / S≤2.5.

[0012] Furthermore, the sum of the mass fraction C of the carbon element and the mass fraction S of the sulfur element in the layered oxide positive electrode material satisfies 700ppm≤C+S≤3100ppm.

[0013] Furthermore, the particle size D of the layered oxide positive electrode material is 50 4μm~20μm.

[0014] Furthermore, the specific surface area of ​​the layered oxide positive electrode material is ≤0.5m 2 / g.

[0015] The present invention further provides a method for preparing the layered oxide positive electrode material, comprising the following steps: mixing a nickel-copper-iron-manganese precursor, a sodium source and an A-containing dopant and then sintering the mixture.

[0016] Furthermore, the theoretical value of the sum of the mass fraction of carbon element and the mass fraction of sulfur element in the layered oxide positive electrode material is γ=3×10 7 ×e y ×TD / (4×T×Me×Sp)±200ppm; where e is a natural constant; TD is the tap density of the nickel-copper-iron-manganese precursor, in g / cm 3 Me is the ratio of the total mass of the metal elements in the nickel-copper-iron-manganese precursor measured by ICP to the mass of the nickel-copper-iron-manganese precursor; Sp is the specific surface area of ​​the nickel-copper-iron-manganese precursor, in m 2 / g; T is the sintering temperature in °C; ±200 is the error coefficient.

[0017] Furthermore, the γ satisfies 700ppm≤γ≤3100ppm.

[0018] Furthermore, the general formula of the nickel-copper-iron-manganese precursor is Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2.

[0019] Furthermore, the tap density TD of the nickel-copper-iron-manganese precursor satisfies 1.6 g / cm 3≤TD≤2.1g / cm 3 .

[0020] Furthermore, the specific surface area Sp of the nickel-copper-iron-manganese precursor satisfies 10m 2 / g≤Sp≤20m 2 / g.

[0021] Furthermore, the particle size D of the nickel-copper-iron-manganese precursor is 50 Satisfy 4μm≤D 50 ≤9μm.

[0022] Furthermore, the sintering temperature T is 900-1000°C.

[0023] Furthermore, the sintering holding time is 10 to 30 hours.

[0024] Furthermore, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.

[0025] The present invention further provides a positive electrode sheet, comprising the layered oxide positive electrode material.

[0026] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The layered oxide positive electrode material provided by the present invention can change the structural strength of the positive electrode material, reduce the dissolution of the Cu element, reduce the content of the CuO impurity phase, and thus improve its electrochemical performance by introducing a specific content of the additive element A.

[0029] (2) Layered oxide positive electrode materials have the advantages of high capacity, good rate performance, and excellent cycle performance after being assembled into batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 The XRD pattern of the layered oxide positive electrode material prepared in Example 2 provided by the present invention;

[0032] Figure 2 This is the XRD diagram of the layered oxide positive electrode material prepared in Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION

[0033] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0034] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0037] In a first aspect, the present invention provides a layered oxide positive electrode material, wherein the layered oxide positive electrode material has a general formula of Na x A y Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 O2.

[0038] Wherein 0.95≤x≤1.05, including but not limited to any one of 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05 or the range between any two of them; 0.001≤y≤0.01, including but not limited to any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01 or the range between any two of them.

[0039] In some specific embodiments, the molar ratio of element A to element Na, y / x≤0.01, including but not limited to any one of 0.01, 0.009, 0.008, 0.006, 0.005, 0.003, 0.002, 0.001, 0.0001 or a range between any two of them.

[0040] Further, A is a doping element, and A includes at least one of Sr, Ca, Ti, Zr, Mo, Nb, Bi, Sb, Y and B, for example, two, three, four, five or more thereof are selected.

[0041] The mass fraction of the copper oxide impurity phase in the layered oxide positive electrode material is ≤0.5%, including but not limited to any one of 0.5%, 0.4%, 0.3%, 0.25%, 0.2%, 0.15%, 0.1%, 0.08%, 0.06%, 0.05%, 0.04%, 0.01%, 0.001% or a range between any two of them.

[0042] The layered oxide positive electrode material provided by the present invention can change the structural strength of the positive electrode material, reduce the dissolution of the Cu element, reduce the content of the CuO impurity phase, and thus improve its electrochemical performance by introducing a specific content of the additive element A.

[0043] Specifically, the battery made of the layered oxide positive electrode material has high capacity, good rate performance and excellent cycle performance.

[0044] In some specific embodiments, the ratio of the mass fraction C of the carbon element to the mass fraction S of the sulfur element in the layered oxide positive electrode material satisfies 1.5≤C / S≤2.5, wherein C / S includes but is not limited to any point value of 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5 or any range value between the two, which is conducive to obtaining better rate performance. It is understood that C and S here refer to the actual contents of carbon and sulfur, respectively, and the actual contents can be measured by an infrared carbon-sulfur analyzer.

[0045] In some specific embodiments, the sum of the mass fraction C of the carbon element and the mass fraction S of the sulfur element in the layered oxide positive electrode material satisfies 700ppm≤C+S≤3100ppm. Wherein C+S includes but is not limited to any point value of 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3100ppm or any range value between the two, which is conducive to further improving the rate performance and cycle performance. Similarly, C and S here refer to the actual contents of carbon and sulfur, respectively.

[0046] In some specific embodiments, the particle size D of the layered oxide positive electrode material is 50 4 μm to 20 μm; including but not limited to any point value of 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm or any range value between two of them. The particle size of the layered oxide positive electrode material is controlled within this range, and has better rate and cycle performance.

[0047] In some specific embodiments, the specific surface area of ​​the layered oxide positive electrode material is ≤0.5 m 2 / g, including but not limited to 0.5m 2 / g, 0.48m 2 / g, 0.45m 2 / g, 0.43m 2 / g, 0.4m 2 / g, 0.38m 2 / g, 0.35m 2 / g, 0.34m 2 / g, 0.33m 2 / g, 0.32m 2 / g, 0.31m 2 / g, 0.3m 2 / g, 0.28m 2 / g, 0.25m 2 / g or any point value or range value between any two of them. The layered oxide positive electrode material provided by the present invention has a smaller specific surface area, can effectively reduce the side reaction with the electrolyte, and improve its cycle performance.

[0048] In some specific embodiments, the 0.1C first discharge capacity of the battery containing the layered oxide positive electrode material is ≥134mAh / g, including but not limited to any one of 134.5mAh / g, 135mAh / g, 135.5mAh / g, 136mAh / g, 137mAh / g, 138mAh / g or any range between two values. The 1C first discharge capacity of the battery containing the layered oxide positive electrode material is ≥124mAh / g, including but not limited to any one of 124.5mAh / g, 125mAh / g, 125.5mAh / g, 126mAh / g, 127mAh / g, 128mAh / g, 129mAh / g, 130mAh / g or any range between two values. The capacity retention rate of a battery containing the layered oxide positive electrode material after 50 cycles at 1C is ≥92%, including but not limited to any point value of 92.4%, 93%, 93.5%, 94%, 94.5%, 95%, 96% or a range value between any two of them.

[0049] In some specific embodiments, the layered oxide positive electrode material is an O3-type layered oxide positive electrode material.

[0050] In a second aspect, the present invention provides a method for preparing the layered oxide positive electrode material, comprising the following steps: mixing a nickel-copper-iron-manganese precursor, a sodium source and an A-containing dopant at a high speed, then sintering once or multiple times, and crushing after cooling to obtain the layered oxide positive electrode material.

[0051] The preparation method has the advantages of short process, simple operation, and mass production.

[0052] In some specific embodiments, the theoretical value of the sum of the theoretical mass fraction C' of the carbon element and the theoretical mass fraction S' of the sulfur element in the layered oxide positive electrode material is γ = C' + S' = 3 × 10 7 ×e y ×TD / (4×T×Me×Sp)±200ppm. The theoretical mass fraction C' of carbon is in ppm, and the theoretical mass fraction S' of sulfur is in ppm. Here, γ is the theoretical total mass ratio of carbon and sulfur. e is a natural constant, an infinite non-repeating decimal, and a transcendental number, with a value of approximately 2.718281828459045. TD is the tap density of the nickel-copper-iron-manganese precursor, in g / cm 3 Me is the ratio of the total mass of the metal elements in the nickel-copper-iron-manganese precursor measured by ICP (i.e., the sum of the masses of the four elements nickel, copper, iron, and manganese obtained by ICP test) to the total mass of the nickel-copper-iron-manganese precursor, hereinafter referred to as the metal total mass. Sp is the specific surface area of ​​the nickel-copper-iron-manganese precursor, in m2 / g. T is the sintering temperature in °C. ±200 is the error coefficient.

[0053] It can be understood that by γ = C' + S' = 3 × 10 7 ×e y The theoretical value of the sum of the mass fractions of carbon and sulfur calculated by the calculation formula of ×TD / (4×T×Me×Sp) differs from the measured value of the sum of the mass fractions of carbon and sulfur by 200 ppm.

[0054] Specifically, the higher the precursor TD, the more difficult it is to remove the internal S through sintering, and the larger the final γ; the higher the sintering temperature T, the easier it is to burn out carbon and sulfur elements, and the smaller the γ value; the higher the precursor metal content Me, the lower the S content, and the lower the γ; the smaller the precursor specific surface area Sp, the denser the surface, the more difficult it is to remove the internal S, and the higher the γ value; the y value has a relatively small impact, which mainly improves the structural strength and reduces the dissolution of Cu.

[0055] In some specific embodiments, the γ satisfies 700ppm≤γ≤3100ppm, and γ includes but is not limited to any point value of 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3100ppm or a range value between any two of them.

[0056] In some specific embodiments, the general formula of the nickel-copper-iron-manganese precursor is Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2.

[0057] In some specific embodiments, the tap density TD of the nickel-copper-iron-manganese precursor satisfies 1.6 g / cm 3 ≤TD≤2.1g / cm 3 ; Including but not limited to 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 , 2.1g / cm 3 In this way, the index of the prepared layered oxide positive electrode material can be within the required range, thereby improving its electrochemical performance and reducing the CuO impurity content.

[0058] In some specific embodiments, the specific surface area Sp of the nickel-copper-iron-manganese precursor satisfies 10m 2 / g≤Sp≤20m 2 / g; but not limited to 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 20m 2 In this way, the index of the prepared layered oxide positive electrode material can be within the required range, thereby improving its electrochemical performance and reducing the CuO impurity content.

[0059] In some specific embodiments, the particle size D of the nickel-copper-iron-manganese precursor is 50 Satisfy 4μm≤D 50 ≤9μm, particle size D 50 Including but not limited to any point value of 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or any range value between two of them. In this way, the index of the prepared layered oxide positive electrode material can be within the required range, thereby improving its electrochemical performance and reducing the CuO impurity content.

[0060] In some specific embodiments, the impurity elements in the nickel-copper-iron-manganese precursor, such as Na, S, Ca, Mg, Al, Zn, Co, Li, etc., are each independently less than 5000 ppm.

[0061] In some specific embodiments, the sodium source includes any Na-containing compound commonly used in the art, such as one or more of sodium carbonate, sodium hydroxide or sodium bicarbonate, but is not limited thereto.

[0062] In some specific embodiments, the A-containing dopant includes any A-containing compound, such as an A-containing oxide, carbonate, hydroxide, etc., but is not limited thereto.

[0063] In some specific embodiments, the sintering temperature T is 900-1000°C, including but not limited to any point value of 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C or a range between any two of them.

[0064] In some specific embodiments, the sintering holding time is 10 to 30 hours, including but not limited to any point value of 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, and 30 hours, or a range value between any two of them.

[0065] In some specific embodiments, the sintering heating rate is 1 to 10°C / min, including but not limited to any point value of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min, 10°C / min, or a range value between any two of them.

[0066] In some specific embodiments, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.

[0067] In a third aspect, the present invention provides a positive electrode sheet comprising the layered oxide positive electrode material.

[0068] The positive electrode sheet has high capacity, good rate performance and excellent cycle performance.

[0069] Optionally, the positive electrode sheet further includes a binder and a conductive agent, which is not limited in the present invention.

[0070] In a fourth aspect, the present invention provides a sodium ion battery comprising the positive electrode sheet.

[0071] The sodium ion battery has excellent electrochemical performance, with the advantages of high capacity, good rate performance, and good cycle stability.

[0072] Optionally, the sodium ion battery further comprises a negative electrode sheet, an electrolyte and a separator, which is not limited in the present invention.

[0073] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0074] Example 1

[0075] The O3 type Na 1.02 Sr 0.01 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2 NiCuFeMn precursor (tap density TD = 1.6 g / cm 3 The total metal content Me was 0.635 and the specific surface area Sp was 13.4 m 2 / g, particle size D 50 =7.4μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel copper iron manganese precursor = 1.02, and weigh the corresponding strontium carbonate additive according to the molar ratio of strontium element to nickel copper iron manganese precursor = 0.01; mix the nickel copper iron manganese precursor, sodium carbonate and strontium carbonate additive in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material. Put the mixed material into an atmosphere furnace, pass compressed air, keep it at 970℃ for 15 hours, then naturally cool it to room temperature, take out the material and crush it to obtain a positive electrode material, whose particle size D 50 The surface area is 9.3 μm and the specific surface area is 0.31 m 2 / g.

[0076] Example 2

[0077] The O3 type Na 1.0 Ca 0.005 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of nickel-copper-iron-manganese precursor Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2(tap density TD=1.95g / cm 3 The total metal content Me was measured by ICP = 0.610, and the specific surface area Sp = 15.6m 2 / g, particle size D 50 =7.6μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel copper iron manganese precursor = 1.0, and weigh the corresponding calcium carbonate additive according to the molar ratio of calcium element to nickel copper iron manganese precursor = 0.005; mix the nickel copper iron manganese precursor, sodium carbonate and calcium carbonate additive in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material. Put the mixed material into an atmosphere furnace, pass compressed air, keep it at 980℃ for 12 hours, then naturally cool it to room temperature, take out the material and crush it to obtain a positive electrode material, whose particle size D 50 The surface area is 9.6 μm and the specific surface area is 0.33 m 2 / g.

[0078] The XRD pattern of the layered oxide positive electrode material prepared in Example 2 is shown in Figure 1 shown.

[0079] Example 3

[0080] The O3 type Na 0.95 Ti 0.002 Ni 2 / 9 Cu1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of nickel-copper-iron-manganese precursor Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2(tap density TD=1.8g / cm 3 The total metal content Me was measured by ICP = 0.634, and the specific surface area Sp = 14.1m 2 / g, particle size D 50 =7.1μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel copper iron manganese precursor = 0.95, weigh the corresponding titanium dioxide additive according to the molar ratio of titanium element to nickel copper iron manganese precursor = 0.002; mix the nickel copper iron manganese precursor, sodium carbonate and titanium dioxide additive in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material. Put the mixed material into an atmosphere furnace, pass compressed air, keep it at 985℃ for 14 hours, then naturally cool it to room temperature, take out the material and crush it to obtain a positive electrode material, its particle size D 50 The surface area is 10.2 μm and the specific surface area is 0.31 m 2 / g.

[0081] Example 4

[0082] The O3 type Na 1.01 Zr 0.002 Y 0.002 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of nickel-copper-iron-manganese precursor Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2(tap density TD = 2.01 g / cm 3 The total metal content Me was measured by ICP = 0.625, and the specific surface area Sp = 18.1m 2 / g, particle size D 50=7.6μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel copper iron manganese precursor = 1.01, weigh the corresponding zirconium dioxide and yttrium trioxide additives according to the molar ratio of zirconium element to nickel copper iron manganese precursor = 0.002, and the molar ratio of yttrium element to nickel copper iron manganese precursor = 0.002; mix the nickel copper iron manganese precursor, sodium carbonate, zirconium dioxide and yttrium trioxide additives in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material. Put the mixed material into an atmosphere furnace, pass compressed air, keep it at 970℃ for 16 hours, then naturally cool it to room temperature, take out the material and crush it to obtain a positive electrode material with a particle size D 50 The surface area is 8.9 μm and the specific surface area is 0.33 m 2 / g.

[0083] Example 5

[0084] The O3 type Na 1.03 B 0.006 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of nickel-copper-iron-manganese precursor Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2(tap density TD=1.7g / cm 3 The total metal content Me was measured by ICP = 0.660, and the specific surface area Sp = 16.1m 2 / g, particle size D 50 =7.1μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel copper iron manganese precursor = 1.03, weigh the corresponding boron oxide additive according to the molar ratio of boron element to nickel copper iron manganese precursor = 0.006; mix the nickel copper iron manganese precursor, sodium carbonate and boron oxide additive in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material. Put the mixed material into an atmosphere furnace, pass compressed air, sinter at 940℃ and keep warm for 20 hours, then naturally cool to room temperature, take out the material and crush it to obtain a positive electrode material with a particle size D 50 The surface area is 9.2 μm and the specific surface area is 0.29 m 2 / g.

[0085] Example 6

[0086] The O3 type Na 0.98 Mo 0.002 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of nickel-copper-iron-manganese precursor Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2(tap density TD = 1.85 g / cm 3 The total metal content Me was measured by ICP = 0.634, and the specific surface area Sp = 18.1m 2 / g, particle size D 50 =6.5μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel copper iron manganese precursor = 0.98, weigh the corresponding molybdenum trioxide additive according to the molar ratio of molybdenum element to nickel copper iron manganese precursor = 0.002; mix the nickel copper iron manganese precursor, sodium carbonate and molybdenum trioxide additive in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material. Put the mixed material into an atmosphere furnace, pass compressed air, sinter at 900℃ and keep warm for 30 hours, then naturally cool to room temperature, take out the material and crush it to obtain a positive electrode material with a particle size D 50 The surface area is 8.8 μm and the specific surface area is 0.34 m 2 / g.

[0087] Example 7

[0088] The O3 type Na 1.05 Sr 0.003 Ti 0.003 Mo 0.003 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material comprises the following steps: weighing a certain amount of nickel-copper-iron-manganese precursor Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2(tap density TD=1.8g / cm 3 The total metal content Me was measured by ICP = 0.642, and the specific surface area Sp = 20m 2 / g, particle size D 50=6.1μm), weigh the corresponding sodium carbonate according to the molar ratio of sodium element to nickel-copper-iron-manganese precursor = 1.05, weigh the corresponding strontium carbonate, titanium dioxide and molybdenum trioxide additives according to the molar ratio of strontium element to nickel-copper-iron-manganese precursor = 0.003, the molar ratio of titanium element to nickel-copper-iron-manganese precursor = 0.003, and the molybdenum element to nickel-copper-iron-manganese precursor = 0.003; mix the nickel-copper-iron-manganese precursor, sodium carbonate with strontium carbonate, titanium dioxide, and molybdenum trioxide additives in a high-speed mixer for 15 minutes, mix until there are no obvious white spots, and take a black-gray mixed material; put the mixed material into an atmosphere furnace, introduce compressed air, keep it at 1000°C for 10 hours, then naturally cool it to room temperature, take out the material and crush it to obtain a positive electrode material, the particle size D 50 The surface area is 10.1 μm and the specific surface area is 0.28 m 2 / g.

[0089] Example 8

[0090] The O3 type Na 1.05 Nb 0.003 Bi 0.003 Sb 0.003 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material is basically the same as that of Example 7, except that: according to the molar ratio of Nb element to nickel copper iron manganese precursor = 0.003, the molar ratio of Bi element to nickel copper iron manganese precursor = 0.003, and the molar ratio of Sb element to nickel copper iron manganese precursor = 0.003, the corresponding niobium pentoxide, bismuth trioxide and antimony trioxide additives are weighed, and the nickel copper iron manganese precursor, sodium carbonate, niobium pentoxide, bismuth trioxide and antimony trioxide additives are mixed in a high-speed mixer. The particle size D of the positive electrode material prepared in this example is 50 The surface area is 9.5 μm and the specific surface area is 0.30 m 2 / g.

[0091] Comparative Example 1

[0092] The O3 type Na 0.95 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of the O2 layered oxide positive electrode material is basically the same as that of Example 3, except that no titanium dioxide additive is added. The particle size D of the positive electrode material prepared in this comparative example is 50 The surface area is 9.7 μm and the specific surface area is 0.36 m 2 / g.

[0093] The XRD pattern of the layered oxide positive electrode material prepared in Comparative Example 1 is shown in Figure 2 shown.

[0094] Comparative Example 2

[0095] The O3 type Na 0.98 Mo 0.002 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of the O2 layered oxide positive electrode material is basically the same as that of Example 6, except that the sintering temperature is replaced with 850°C. The particle size D of the positive electrode material prepared in this comparative example is 50 The surface area is 8.1 μm and the specific surface area is 0.43 m 2 / g.

[0096] Comparative Example 3

[0097] The O3 type Na 1.03 B 0.006 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of the O2 layered oxide positive electrode material is basically the same as that of Example 5, except that the sintering temperature is replaced with 1050°C. The particle size D of the positive electrode material prepared in this comparative example is 50 The surface area is 12.2 μm and the specific surface area is 0.34 m 2 / g.

[0098] Comparative Example 4

[0099] The O3 type Na 1.01 Zr 0.02 Y 0.02 Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The preparation method of the O2 layered oxide positive electrode material is basically the same as that of Example 4, except that: the corresponding zirconium dioxide and yttrium trioxide additives are weighed according to the molar ratio of zirconium element to nickel copper iron manganese precursor = 0.02, and the molar ratio of yttrium element to nickel copper iron manganese precursor = 0.02. The particle size D of the positive electrode material prepared in this comparative example 50 The surface area is 8.8 μm and the specific surface area is 0.33 m 2 / g.

[0100] Comparative Example 5

[0101] The O3 type Na 1.02 Sr 0.01 Ni 2 / 9 Cu 1 / 9 Fe1 / 3 Mn 1 / 3 The preparation method of O2 layered oxide positive electrode material is basically the same as that of Example 1, except that: Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The tap density of (OH)2 nickel copper iron manganese precursor is TD = 1.5 g / cm 3 The total metal content Me was 0.631 and the specific surface area Sp was 25.0 m 2 / g, particle size D 50 =3.5 μm. The particle size D of the positive electrode material prepared in this comparative example 50 The surface area is 9.3 μm and the specific surface area is 0.38 m 2 / g.

[0102] In the present invention, the particle size D 50 The test was conducted using a Malvern laser particle size analyzer. The actual content of carbon and sulfur was measured using an infrared carbon-sulfur analyzer. The XRD test was conducted using a Bruker D8 ADVANCE device with a scanning range of 10-80°, and the copper oxide impurity content was obtained using Jade, X-Ray, and Highscore analysis software. The specific surface area test was conducted using a precision high-performance surface area analyzer, and the test was conducted with reference to GB / T19587-2017 "Determination of the Specific Surface Area of ​​Solids by Gas Adsorption BET Method". The specific surface area of ​​the material was tested using a precision high-performance JW-DX dynamic adsorption specific surface area analyzer. 1 g of sample was weighed, the heating temperature was set to 150°C, the degassing time was 60 min, and the specific surface area data output after calculation by the software was recorded. The tap density test was conducted using a Quanta density tap compactor. The metal content test was conducted using an ICP test.

[0103] The physical and chemical indicators of the precursors used in the above embodiments and comparative examples (tap density TD, unit: g / cm 3 ; Specific surface area Sp, unit is m 2 / g; metal content Me) and sintering temperature T (in °C) are shown in Table 1. According to the physical and chemical indicators of the precursor and the sintering temperature, the theoretical value γ of the sum of the mass fraction of carbon and the mass fraction of sulfur in the layered oxide positive electrode material is calculated, where γ = 3×10 7 ×e y×TD / (4×T×Me×Sp)ppm, the results are shown in Table 1. At the same time, the y value (i.e., the molar content of the doping element A) in the general formula of the layered oxide positive electrode materials prepared in each embodiment and each comparative example, and the value of y / x (the molar ratio of the A element to the Na element) are shown in Table 1. In addition, the mass fraction C of the carbon element and the mass fraction S of the sulfur element in the layered oxide positive electrode materials prepared in each embodiment and each comparative example were tested respectively, and C / S was calculated, and the results are shown in Table 1.

[0104] Table 1 Comparison of key parameters

[0105]

[0106]

[0107] Furthermore, the mass fraction of the copper oxide impurity phase in the layered oxide positive electrode materials prepared in each embodiment and each comparative example was detected, and the results are shown in Table 2.

[0108] The layered oxide positive electrode materials prepared in each embodiment and each comparative example are used as active materials and assembled into button cells according to the following method: the active material, the conductive agent Super P, and the adhesive PVDF are used in a mass ratio of 90:5:5 to prepare the positive electrode material slurry using a degassing machine, and the solid content of the slurry is adjusted to 39% by N-methylpyrrolidone (NMP), and the adjusted slurry is coated on aluminum foil using an automatic coating machine, dried at 120°C in a vacuum drying oven, and then rolled by a roller press, punched by a slicer, and assembled into button 2032 batteries in a glove box. The electrolyte is 1.2 mol / L NaPF6, wherein the solvent is EC:PC:EMC=1:1:1 (volume ratio), and 2wt.% FEC is added, the diaphragm is a glass fiber diaphragm, and a metal sodium sheet is used as the counter electrode. Each button half-cell was tested for charge and discharge in the voltage range of 2.5 to 4.05 V on a Xinwei tester: 0.1C charge and discharge for 3 times, and then 1C charge and discharge test, 0.1C first discharge capacity and first cycle charge and discharge efficiency, as well as capacity retention after 50 cycles at 1C were tested. The test results are shown in Table 2.

[0109] Table 2 Mass fraction of CuO in positive electrode materials and electrochemical performance test results

[0110]

[0111]

[0112] By comparing Example 3 with Comparative Example 1, it is shown that the single crystal material without doping is more likely to have CuO impurity phase. However, after doping with element A in Example 3, the content of CuO impurity phase is significantly reduced.

[0113] By comparing Example 6 with Comparative Example 2, and Example 5 with Comparative Example 3, it is shown that too low or too high a temperature will lead to an increase in the CuO content, and at the same time, the C / S value is too high, resulting in poor battery performance.

[0114] By comparing Example 4 with Comparative Example 4, it is shown that excessive additives will also lead to the appearance of CuO impurity phase, affecting battery performance.

[0115] By comparing Example 1 with Comparative Example 5, it is shown that the physical and chemical indicators of the nickel-copper-iron-manganese precursor will also lead to the appearance of CuO impurity phase, affecting the battery performance.

[0116] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A layered oxide positive electrode material, characterized in that: The general formula of the layered oxide positive electrode material is Na x A y Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 O2; wherein 0.95≤x≤1.05, 0.001≤y≤0.01, and A includes at least one doping element selected from the group consisting of Sr, Ca, Ti, Zr, Mo, Nb, Bi, Sb, Y, and B; The mass fraction of the copper oxide impurity phase in the layered oxide positive electrode material is ≤0.5%.

2. The layered oxide positive electrode material according to claim 1, characterized in that: The ratio of the mass fraction C of the carbon element to the mass fraction S of the sulfur element in the layered oxide positive electrode material satisfies 1.5≤C / S≤2.5; And / or, the sum of the mass fraction C of the carbon element and the mass fraction S of the sulfur element in the layered oxide positive electrode material satisfies 700ppm≤C+S≤3100ppm.

3. The layered oxide positive electrode material according to claim 1, characterized in that: The particle size D of the layered oxide positive electrode material 50 4μm~20μm; And / or, the specific surface area of ​​the layered oxide positive electrode material is ≤0.5m 2 / g.

4. The method for preparing a layered oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing a nickel-copper-iron-manganese precursor, a sodium source and an A-containing dopant and then sintering the mixture.

5. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: The theoretical value of the sum of the mass fraction of carbon element and the mass fraction of sulfur element in the layered oxide positive electrode material is γ=3×10 7 ×e y ×TD / (4×T×Me×Sp)±200ppm; where e is a natural constant; TD is the tap density of the nickel-copper-iron-manganese precursor, in g / cm 3 Me is the ratio of the total mass of the metal elements in the nickel-copper-iron-manganese precursor measured by ICP to the mass of the nickel-copper-iron-manganese precursor; Sp is the specific surface area of ​​the nickel-copper-iron-manganese precursor, in m 2 / g; T is the sintering temperature in °C; ±200 is the error coefficient.

6. The method for preparing the layered oxide positive electrode material according to claim 5, characterized in that: The γ satisfies 700ppm≤γ≤3100ppm.

7. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: (1) The general formula of the nickel-copper-iron-manganese precursor is Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2; (2) The tap density TD of the nickel-copper-iron-manganese precursor satisfies 1.6 g / cm 3 ≤TD≤2.1g / cm 3 ; (3) The specific surface area Sp of the nickel-copper-iron-manganese precursor satisfies 10m 2 / g≤Sp≤20m 2 / g; (4) The particle size D of the nickel-copper-iron-manganese precursor 50 Satisfy 4μm≤D 50 ≤9μm.

8. The method for preparing the layered oxide positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: (1) The sintering temperature T is 900-1000° C.; (2) The sintering holding time is 10 to 30 hours; (3) The sintering atmosphere includes air atmosphere and / or oxygen atmosphere.

9. A positive electrode sheet, characterized in that: The invention comprises the layered oxide positive electrode material as claimed in any one of claims 1 to 3.

10. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.